2020
DOI: 10.1007/s10157-020-01879-8
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum calcium or phosphate levels and mortality stratified by parathyroid hormone level: an analysis from the MBD-5D study

Abstract: Introduction There is limited evidence about the association between calcium and phosphate levels and mortality stratified by intact parathyroid hormone (iPTH) level. Methods We investigated whether differences in iPTH level affect the relationship between calcium and phosphate levels and all-cause mortality in hemodialysis patients with secondary hyperparathyroidism (SHPT). Calcium and phosphate levels were categorized as low (< 8.5 mg/dL, < 4.0 mg/dL), medium (≥ 8.5-< 9.5 mg/dL, ≥ 4.0-< 7.0 mg/dL), and high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Previous observational data suggested an association between abnormal biochemical markers of mineral metabolism and death [18][19][20][21][22]. However, the results of these studies were inconsistent [23][24][25][26][27][28]. Covic et al [29] made a meta-analysis with 19 studies that assessed the association between disturbances in biochemical parameters and all-cause mortality among patients on dialysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous observational data suggested an association between abnormal biochemical markers of mineral metabolism and death [18][19][20][21][22]. However, the results of these studies were inconsistent [23][24][25][26][27][28]. Covic et al [29] made a meta-analysis with 19 studies that assessed the association between disturbances in biochemical parameters and all-cause mortality among patients on dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous observational data suggested an association between abnormal biochemical markers of mineral metabolism and death [ 18–22 ]. However, the results of these studies were inconsistent [ 23–28 ]. Covic et al.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown the importance of starting treatment at lower phosphorus and PTH levels on long-term outcomes of SHPT and the ability to manage the disease and subsequent sequelae. [2][3][4]20 While prior research has shown that etelcalcetide is effective at all levels of severity of SHPT, the ability to achieve target goals was greatest, and dose requirement smallest, when etelcalcetide was initiated among patients with the lowest level of disease severity, as defined by PTH concentrations below 600 pg/ml at baseline. 21 Unmanaged SHPT may lead to parathyroidectomy, with the associated costs of an invasive surgery, and which encompasses additional complications and risk of cardiovascular events and hungry bone syndrome in dialysis patients.…”
Section: Discussionmentioning
confidence: 98%
“…1 Research has shown that consistent control of the three mineral and bone disease (MBD) biochemical parameters-PTH, calcium, and phosphorus-in hemodialysis patients was associated with better survival and improvements in other outcomes. [2][3][4] Calcimimetics are a class of drugs that reduce levels of PTH. Two calcimimetics-oral cinacalcet (Sensipar, Amgen, Thousand Oaks, CA) and intravenous etelcalcetide (Parsabiv, Amgen, Thousand Oaks, CA)-are approved for use in the United States.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation